Fine needle aspiration cytology of metastatic renal cell carcinoma - a case report - Wan Muhaizan Wan Mustaffa,; Sharifah Noor Akmal Syed Husain, (Penerbit UKM, 2006)
Fine needle aspiration cytology under radiologic guidance for diagnosis of renal cell carcinoma is well established and is increasingly utilized. This is because renal cell carcinoma displays fairly characteristic cellular features permitting correct cytologic identification. We present a case of a 66-year-old man who had advanced renal cell carcinoma with spread to aortic and cervical lymph nodes, lungs and liver. Fine needle aspiration cytology of the para-aortic mass showed tight clusters of malignant cells with abundant and vacuolated cytoplasm consistent with renal cell carcinoma. Histology of the left cervical lymph nodes together with immunohistochemistry findings were consistent with the cytologic diagnosis of metastatic renal cell carcinoma. The patient succumb to his illness three years after the diagnosis was made